Performance Appraisal. - Abraham, Akampurira (Diplomica Verlag, 2014)
The study was carried out to investigate the effectiveness of teachers' performances in secondary schools. This investigation is based upon the methods of qualitative and quantitative approaches, and is carried out amongst selected schools in Kabale Municipality, in the period from 2008 to 2009. The study investigates the teachers' attitudes towards appraisal schemes, the effect of feedback on implementation of the appraisal schemes, problems faced while conducting performance appraisal, and the role of appraisal design. Auszug aus dem Text Text Sample: Chapter 2.4.3,